PEMBUATAN PROGRAM APLIKASI WEBSITE GEREJA DAMAI KRISTUS - Agnes Agnes (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Website is a technology that can change operational activities in profit organization or non-profit organization. Practically, many organizations use website to share information. Damai Kristus Church is a non-profit organization. It isn’t have a website. The purpose of this study is to provide information about church’s profile, news, activities and schedules.This study aims to develop Damai Kristus Church’s website to help them to share information about their profil, schedules,and activities. The findings indicated that Damai Kristus church’s website can help people to search information about Damai Kristus church’s website vision & mission, history, holy mass schedules, activities, announcement, parish council, and news. In the other hand,this website is used to become one of media to introduce Damai Kristus Church to another people